2019
DOI: 10.1099/jgv.0.001341
|View full text |Cite
|
Sign up to set email alerts
|

To TRIM or not to TRIM: the balance of host–virus interactions mediated by the ubiquitin system

Abstract: The innate immune system responds rapidly to protect against viral infections, but an overactive response can cause harmful damage. To avoid this, the response is tightly regulated by post-translational modifications (PTMs). The ubiquitin system represents a powerful PTM machinery that allows for the reversible linkage of ubiquitin to activate and deactivate a target's function. A precise enzymatic cascade of ubiquitin-activating, conjugating and ligating enzymes facilitates ubiquitination. Viruses have evolve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 203 publications
(514 reference statements)
1
48
0
Order By: Relevance
“…The presence of autoantibodies against cancerassociated TRIMs accords with the strong temporal association between myositis and the development of malignancies in adult-onset anti-TIF1γ positive DM (Oldroyd et al, 2019), consistent with the high proportion of cancer-associated myositis cases in the current study (45%). Overall, the expanded targeting of TRIM proteins we observed in DM plasma supports the role of the TRIM RING-type E3 ubiquitin ligase subfamily as powerful regulators of the immune system through post-translational modification (Hage and Rajsbaum, 2019;van Tol et al, 2017).…”
Section: Discussionsupporting
confidence: 70%
“…The presence of autoantibodies against cancerassociated TRIMs accords with the strong temporal association between myositis and the development of malignancies in adult-onset anti-TIF1γ positive DM (Oldroyd et al, 2019), consistent with the high proportion of cancer-associated myositis cases in the current study (45%). Overall, the expanded targeting of TRIM proteins we observed in DM plasma supports the role of the TRIM RING-type E3 ubiquitin ligase subfamily as powerful regulators of the immune system through post-translational modification (Hage and Rajsbaum, 2019;van Tol et al, 2017).…”
Section: Discussionsupporting
confidence: 70%
“…In the present study, we have developed an innovative and modularized targeted protein degradation system, the Predator system, based on the core function of Trim21 (17,19,39), and we demonstrated that this novel method could directly degrade endogenous target proteins in cells with high efficiency. Compared to Trim-Away technology which introduces antibodies into cells by microinjection or electroporation, our Predator system, through ectopic expression of modularized bifunctional molecules that functions similarly as the antibody to recruit E3 ligase Trim21 and bind to the targets with high specificity, was much more modularized and convenient, because it need only to express the designed Predator system via easy-to-use gene vectors like plasmids or virus (Fig 6) (9).…”
Section: Discussionmentioning
confidence: 89%
“…In addition, this study identified the E3-ligase TRIM25, an important mediator of anti-viral activity [ 36 , 37 ], as a mediator of CIC post-translational stability. Overexpression of TRIM25 was able to reduce CIC protein expression while siRNA knockdown of TRIM25 was able to stabilize CIC and promote its tumor suppressor function.…”
Section: Discussionmentioning
confidence: 99%